2018
DOI: 10.56093/ijans.v88i3.78254
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Frieswal cattle: A crossbred dairy animal of India

Abstract: Frieswal cattle is one of the crossbred strains having 5/8 Holstein Friesian and 3/8 Sahiwal inheritance, develo pedby ICAR-Central Institute for Research on Cattle, Meerut, in collaboration with Ministry of Defence. The projectwas started in 1987 for the evolution of a new crossbred national milch breed: Frieswal – (Holstein×Sahiwal), yielding 4,000 kg of milk with 4% butter fat in a mature lactation of 300 days. It is the only project in the country where such a huge population of animals (more than 20,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Animal calved during the period 1997-2001 had significantly higher milk yield and peak yield (3634.15±26.56 and 16.57±0.10 kg) followed by period 2002-2007 (3353.64±18.78 and 15.87±0.07 kg). The significant effects of period of calving (Gaur et al 2008, Komatwar et al 2010and Kumar et al 2015 and season of calving (Gaur 2007 andKumar et al 2015) on milk yield were reported in previous studies. The variation in total milk yield (decrease over the periods) was primarily due to the shortening of lactation length (340.36 days during 1991-1996 to 303.89 days during 2007-2012).…”
mentioning
confidence: 71%
“…Animal calved during the period 1997-2001 had significantly higher milk yield and peak yield (3634.15±26.56 and 16.57±0.10 kg) followed by period 2002-2007 (3353.64±18.78 and 15.87±0.07 kg). The significant effects of period of calving (Gaur et al 2008, Komatwar et al 2010and Kumar et al 2015 and season of calving (Gaur 2007 andKumar et al 2015) on milk yield were reported in previous studies. The variation in total milk yield (decrease over the periods) was primarily due to the shortening of lactation length (340.36 days during 1991-1996 to 303.89 days during 2007-2012).…”
mentioning
confidence: 71%
“…The performance of the animals during the initial period was lowest (3389.81±40.53 kg), indicating the positive genetic trend of milk production over years. The significant effects of period of calving (Gaur et al 2008, Komatwar et al 2010, Kumar et al 2015 and season of calving (Gaur 2007, Kumar et al 2015 on milk yield were reported in previous studies.…”
mentioning
confidence: 71%
“…Animals used in present study were B. taurus × B. indicus crossbred dairy bulls ( N = 378), popularly named as ‘Frieswal’. Frieswal cows were evolved by systematic breeding of Holstein Friesian (HF) and Sahiwal, stabilized over the generations and have 62.5% HF and 37.5% Sahiwal (Kumar et al., 2018). The age of bulls ranged from 6 to 91 months.…”
Section: Methodsmentioning
confidence: 99%